Lakuna dalam pemakaian dalihan ketidakmatangan menurut undang-undang jenayah di Malaysia - Anita Abdul Rahim, (Fakulti Undang - Undang, 2010)
The Malaysian law has provided a specific defence to a child offender within the ages of ten to twelve. Nevertheless, the accused child must prove that at the time of committing the crime, he or she has not attained sufficient maturity of understanding to judge the nature and consequence of the act. How is ‘immaturity’ defined by the courts and how do the courts apply this particular defence to exempt the child from his or her criminal liability? These questions are highlighted in this article and it is submitted that the Malaysian courts have never interpreted ‘ immaturity’ in the provision of section 83 of the Malaysian Penal Code, which subsequently leads to the finding that its application is vague and ambiguous